Integrated Analysis of DEAD-Box Helicase 56: A Potential Oncogene in Osteosarcoma - Zhu, Chen; Zhang, Xianzuo; Kourkoumelis, Nikolaos; Shen, Yong; Huang, Wei (Frontiers in Bioengineering and Biotechnology, 2020)
Background: Osteosarcoma is a solid tumor common in the musculoskeletal system. The DEAD-box helicase (DDX) families play an important role in tumor genesis and proliferation. Objective:To screen potential molecular targets in osteosarcoma and elucidate its relationship with DDX56. Methods: We employed the Gene Expression Omnibus and The Cancer Genome Atlas datasets for preliminary screening. DDX56 expression was measured by RT-qPCR in three osteosarcoma cell lines. Biological roles of DDX56 were explored by Gene ontology, Kyoto Encyclopedia of Genes and Genomes and Ingenuity Pathway Analysis. Cell proliferation, cycle, and apoptosis assays were performed using Lentivirus™ knockdown technique. Results: It was found that DDX56 expression was regularly upregulated in osteosarcoma tissue and cell lines, while DDX56 knockdown inhibited cell proliferation and promoted cell apoptosis. Conclusions: The findings suggest DDX56 as a potential therapeutic target for the treatment of osteosarcoma.